Slappy birthday to you - Stine, R. L. (New York : Scholastic Inc., 2017)
It's bad enough Ian Barker has to spend his twelfth birthday with his sister and their two annoying cousins. The four of them can't ever hang out without getting into trouble. But when Ian gets a Slappy dummy from his dad, things go from bad to worse. When Slappy's in charge, you don't fight over him, he fights over you.
School Library Journal, February 2017
Publisher's Weekly, November 2016
Booklist, December 2016
Kirkus Review, November 2016
3-6
490L
Keywords: Ventriloquists' dummies -- Fiction; Birthdays -- Fiction; Cousins -- Fiction; Ventriloquists' dummies -- Fiction; Puppets and puppet plays -- Fiction; Birthdays -- Fiction; Cousins -- Fiction; Horror fiction